Manajemen Program Pengembangan Kompetensi Profesional Guru Upaya utuk Meningkatkan Mutu Pendidikan di Sekolah Dasar Muhammadiyah 1 Tenggarong (Syntax Idea)
This study aims to determine (1) planning of teacher professional competency development programs to inprove the quality of education (2) strategies for implementing teacher professional competency develoment programs to improve the quality of education. Data collection techniques through: observation, interviews, and documentation. The subjectts of this study were the principal, class teacher and subject teacher. Data were analyzed by data reduction, data display, drawing conclusions, and data verification. The results of the study show: (1) program planning starts from analyzing the ablity of teachers the needs of teachers from external and internal factors as teacher upgrading, teachir seminars twg (teacher working group), and workshops. (2) the strategy undertalken is to make the stages of the strategy, namely the implementation of compiled prggrams, approaching all teachers and employee and direct supervision of school proggrams.